12th Grader’s Perception Regarding Tertiary Students Teaching Practices - Putu Wahyu Sudewi; Adi Isma; Reski Reski (Hasanuddin University, 2024)
This research investigates students' perceptions of the teaching skills of teaching assistant (TA) tertiary students from the English Education Study Program at the University of Sulawesi Barat, conducted at SMA Negeri 1 Majene. The study aims to assess how well these TA tertiary students perform in key teaching areas, including lesson opening and closing, explaining, questioning, providing reinforcement, introducing variety, guiding small group discussions, and classroom management. Using a qualitative approach, data were collected via questionnaires based on a Likert scale, complemented by guided interviews for qualitative insights. The findings reveal that TA tertiary students received high ratings in explaining (92%), questioning (84%), and classroom management (85%), with an overall average rating of 81.37%, categorized as